Legal Analysis of Religious Transfer As A Reason For Divorce In Islam - M. Abdurrahman Husain Al Habsyi; Abdul Rachmad Budiono; Nur Chanifah (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study examines the legal issues of divorce in the context of domestic conflict triggered by religious conversion within Islam, which has not been explicitly regulated as a ground for divorce in Indonesian positive law. The study focuses on how the open-textured norm of Article 116 letter (f) of the Compilation of Islamic Law is interpreted in judicial practice, and its implications for legal certainty. The research method used is normative juridical with a statutory, conceptual, and case-based approach, to analyze the adequacy of the norm and the construction of its application by judges. The results of the discussion indicate that religious conversion cannot be used as a direct reason for divorce, but is only relevant if it causes continuous disputes and quarrels that impact household disharmony. However, the absence of operational parameters in the norm leaves room for judicial discretion and has the potential to lead to inconsistent decisions. Therefore, strengthening through the formulation of operational parameters that can guide judges' assessments in a more structured manner, including by adopting a preventive approach that considers early indications of conflict. These parameters include aspects of conflict escalation, ideological depth, impact on family function, and the possibility of disharmony rationally. Theoretically, this construction aligns with the principles of legal certainty and progressive law that is responsive to social dynamics. For implementation, these parameters should ideally be formulated in a Supreme Court Regulation as an interpretive guideline to improve the consistency, predictability, and quality of decisions in the religious courts